THE RELATIONSHIP OF KNOWLEDGE, ATTITUDE AND PERIOD OF WORK WITH THE ACTIONS OF HEALTH PERSONNEL IN MEDICAL WASTE MANAGEMENT - Septi Fitriyanti; Elwan Chandra; Eka Joni Yansyah; Sabtian Sarwoko (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2025)
Puskesmas as a public service facility that can pollute the environment and allow the spread of disease. The aim is to determine the connection among information, attitudes, and period of provider of medical examiners with their movements in medical waste at the Sekar Jaya Community Health Center, Ogan Komering Ulu Regency in 2024. This study adopted an analytic survey with a cross-sectional design. For data analysis at the univariate as well as bivariate levels, the chi-square test was used. This study involved 108 health workers at Sekar Jaya Health Center. The results of univariate analysis showed that 85 respondents (78.7%) were health workers who acted well, 78 respondents (72.2%) had a good level of knowledge. In addition, there were 73 respondents (67.6%) who showed a positive attitude, and 77 respondents (71.3%) had a working period of ≥5 years. Further analysis showed that there was a relationship between the level of knowledge and the actions of health workers as indicated by a P value of 0.07, the relationship between attitude and the actions of health workers was obtained with a P value of 0.011, and the relationship between tenure with the actions of health workers was obtained with a P value of 0.043. From these results, it can be concluded that between the level of knowledge, attitude, and tenure of work on medical waste management at the Sekar Jaya Health Center, Ogan Komering Ulu Regency in 2024 there is a significant relationship. Therefore, it is recommended for the Puskesmas to organize training or seminars to improve the competence of health workers in medical waste management.